The Morning After : videoarbeiten der Sammlung Goetz - Weserburg Museum, Bremen (Bremen : Weserburg Museum für moderne kunst Bremen, 2008)
Antoni, Janine ; Brech, Christoph ; Cavusoglu, Ergin ; Claerbout, David ; Doherty, Willie ; Grimonprez, Johan ; Hatoum, Mona ; Hubbard, Teresa ; Birchler, Alexander ; Leutenegger, Zilla ; McCaslin, Matthew ; Müller, Matthias ; Olivier, Jacco ; Oursler, Tony ; Pfeiffer, Paul ; Rhode, Robin ; Sala, Anri ; Stürmer, Frank
Exhibition in Weserburg Museum, Bremen, 12.04.2008 - 17.08.2008
Duits en Engels
boek